New Reference Materials and Assessment of Matrix Effects for SIMS Measurements of Oxygen Isotopes in Garnet. Issue 3 (15th May 2020) - Vho, Alice; Rubatto, Daniela; Putlitz, Benita; Bouvier, Anne‐Sophie
Abstract : Accurate ion microprobe analysis of oxygen isotope ratios in garnet requires appropriate reference materials to correct for instrumental mass fractionation that partly depends on the garnet chemistry (matrix effect). The matrix effect correlated with grossular, spessartine and andradite components was characterised for the Cameca IMS 1280HR at the SwissSIMS laboratory based on sixteen reference garnet samples. The correlations fit a second‐degree polynomial with maximum bias of ca . 4‰, 2‰ and 8‰, respectively. While the grossular composition range 0–25% is adequately covered by available reference materials, there is a paucity of them for intermediate compositions. We characterise three new garnet reference materials GRS2, GRS‐JH2 and CAP02 with a grossular content of 88.3 ± 1.2% (2 s ), 83.3 ± 0.8% and 32.5 ± 3.0%, respectively. Their micro scale homogeneity in oxygen isotope composition was evaluated by multiple SIMS sessions. The reference δ 18 O value was determined by CO2 laser fluorination (δ 18 OLF ). GRS2 has δ 18 OLF  = 8.01 ± 0.10‰ (2 s ) and repeatability within each SIMS session of 0.30–0.60‰ (2 s ), GRS‐JH2 has δ 18 OLF  = 18.70 ± 0.08‰ and repeatability of 0.24–0.42‰ and CAP02 has δ 18 OLF  = 4.64 ± 0.16‰ and repeatability of 0.40–0.46‰. Key Points: Three new garnet reference materials with Grs >30% for in situ oxygen isotope measurement by ion microprobe are characterised. Matrix effect associated with Grs, Sps and And components is quantified for the ion microprobe at the SwissSIMS laboratory. Matrix effects across different sessions and laboratories are most reproducible for Grs <50%, Sps <20% and And over the entire range.